Isocyanate‐Free Curing of Glycidyl Azide Polymer with Bis–propargylhydroquinone. Issue 4 (23rd December 2016) - Sonawane, Sanjeevani; Anniyappan, M.; Athar, Javaid; Singh, Avtar; Talawar, M. B.; Sinha, R. K.; Banerjee, Shaibal; Sikder, A. K.
Abstract: Bis‐propargylhydroquinone (BPHQ) is an alkyne functionalized isocyanate‐free curing agent for hydroxyl terminated azido polymers. Conventionally, glycidyl azide polymer (GAP) is cured by isocyanate based curatives, which are toxic and hygroscopic in nature. The reaction between hydroxyl end group of GAP and isocyanate is highly sensitive to moisture causing voids in the propellant, leading to poor mechanical properties. Herein, an alternate approach was adapted to exploit 1, 3‐dipolar cycloaddition reaction between azido group of GAP and the triple bond (–C≡CH) of BPHQ without catalyst at 50 °C forming triazole crosslinked polymer. The curing behavior of GAP‐BPHQ system was studied by rheological method and based on the results the gel time was determined. In addition, the reaction between GAP and BPHQ was carried out with various GAP/BPHQ ratios (0.9 to 2.5) and effects on mechanical properties of resulting triazole polymers were investigated. Post curing hardness of GAP‐BPHQ binder system was tested by surface Shore‐A hardness measurement. The compatibility of BPHQ with energetic oxidizers such as ammonium dinitramide (ADN) and hydrazinium nitroformate (HNF) were also studied by differential scanning calorimetery (DSC) technique and showed good compatibility. The activation energy ( E a ) of cured GAP‐BPHQ binder was evaluated by DSC using Ozawa and Kissinger methods and are found to be 33.55 and 33.16 kcal mol –1, respectively. The advantage of this curing system between GAP and BPHQ is unaffected by moisture as compared to isocyanate based urethane systems and also no need to control humidity during the processing of propellant. The experimental results reveal that triazole crosslinked polymer system could be a better choice to develop novel energetic binder systems for explosives as well as propellants composition with improved performance and eco‐friendly nature. Abstract :